On violence : a reader - Lawrence, Bruce B.; Karim, Aisha, 1968- (e-Duke books scholarly collection., 2007)
This anthology brings together classic perspectives on violence, putting into productive conversation the thought of well-known theorists and activists, and proceeds from the editor's contention that violence is always historically contingent; it must be contextualized to be understood.